STRATEGI DIGITAL BRANDING PRODUK UMKM RAMAH LINGKUNGAN MELALUI KONTEN KREATIF TIKTOK DAN INSTAGRAM - Nazwa Labagow; Marsel Rampalimbo; Nadya Ugis; Felia Rumate, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2025)
The development of social media has changed the way products are promoted, especially for Micro, Small, and Medium Enterprises (MSMEs) that require effective and cost-efficient marketing strategies. Many MSMEs struggle to build a strong brand image amidst the increasing consumer awareness of eco-friendly products, especially among the younger generation. This research aims to design and implement a digital branding strategy based on creative content through TikTok and Instagram Reels to enhance the appeal and brand awareness of environmentally friendly MSME products. The method used is descriptive research with a case study approach on a local MSME partner. Data collection techniques include direct observation, video content creation, social media engagement analysis, and consumer surveys through online questionnaires. The research results show that short visual content is effective in influencing consumer perception and purchase interest, as well as increasing engagement on social media platforms. The conclusion of this research is that simple and creative digital marketing strategies can be replicated by other SMEs, providing real contributions to vocational students in facing digital marketing challenges and promoting sustainable SME empowerment.